Evaluation of Tp-e interval and Tp-e/ QTc ratio in patients with mild to moderate psoriasis - Arican Ozluk, Ozlem; Yilmaz, Mustafa; Topal, Dursun; Tenekecioglu, Erhan; Kanat, Selcuk; Vatansever, Fahriye; Peker, Tezcan; Karaagac, Kemal; Boyraz, Bedrettin (The European Research Journal, 2016)
Objectives. Many systemic diseases including cardiovascular disturbances have been described in psoriatic patients. In the previous studies, left ventricle (LV) subclinical myocardial dysfunction was reported in the psoriasis patients. The T-wave peak to end (Tp-e) interval is a relatively new marker for ventricular arrhythmogenesis and repolarization heterogeneity. Prolongation of this interval represents a period of potential vulnerability to ventricular arrhythmias. However, there is no information available assessing the Tp-e interval and related calculations in patients with psoriasis disease. The aim of this study was to evaluate ventricular repolarization in patients with psoriasis disease by using QT, corrected QT (QTc) and Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio. Methods. In this study, retrospective analysis of 30 patients who underwent the psoriasis treatment and of 30 healthy individuals was performed. The severity of the disease was evaluated by the “Psoriasis Area and Severity Index”. QT, corrected QT (QTc), Tp-e interval and Tp-e/QT ratio were measured by means of the 12-lead electrocardiogram. Left ventricular function was evaluated by echocardiography. Results. Baseline characteristics and QT and QTc intervals were similar in both groups. No difference was detected between the groups with regards to Tp-e interval (83.0±9 vs 82.3±10; p=0.81), Tp-e/QT (0.22±0.03 vs 0.23±0.04; p=0.3) and Tp-Te/QTc (0.20±0.04 vs 0.19±0.04; p=0.77). Conclusions. These findings suggest that ventricular repolarization in mild to moderate psoriasis patients might be unimpaired. Larger samples and severe degree psoriasis patients are needed to evaluate the arrhythmia risk in psoriasis patients.